Chapter 36 Urban struggles and theorising from Eastern European cities A collective interview with Ana Vilenica, Ioana Florea, Veda Popovici and Zsuzsi Pósfai - Lancione, Michele; Mcfarlane, Colin (Taylor & Francis, 2021)
Eastern Europe, activism, housing, urban policies, urban power structures, spacial justice, global urbanism